Adverse drug reactions in hospitalized paediatric patients in a tertiary care center in Kerala, India - N., Shiva Murthy; Jose, Praveen V.; S., Basalingappa; Ali, Safeera K.; V. K., Mabel Elizabeth (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drug safety information about children is scarcely available. This study aims to describe the ADRs in hospitalized paediatric patients under 12 years of age in paediatrics wards of DM WIMS Hospital, Wayanad, Kerala, a tertiary care center in southern part of India. Methods: A retrospective study based on data collected as per the ongoing pharmacovigilance program of India (PvPI) was conducted for twelve months period in order to study the ADRs in hospitalized paediatric patients under 12 years of age with at least one medication prescribed. The study was conducted in paediatrics wards of DM WIMS Hospital, Wayanad. WHO-UMC scale and Naranjo´s Algorithm was used to evaluate causality, the modified Hartwig and Siegel assessment scale was used to establish severity and the Schumock and Thornton criteria was used to determine preventability. Results: Forty-two children (42) who experienced 55 ADRs were included in the study. The frequency was higher in children under 1 year of age (47.62%). Emergence of ADRs was higher in male patients (59.52%), in those used three or more medicines together (71.43%) and in those with systemic antibiotics (58.18%). Conclusions: Being the first study from Kerala in paediatric patients, it is an important contribution to drug safety profile in children from this region of India. ADRs frequency and other descriptive characteristics are provided for the enrolled children under 12 years of age. ADRs are an additional burden of morbidity and risk, particularly in those who used several medicines, including antibiotics.